Reflective Practice in Language Teaching and Learning: A Literature Review - Mali, Yustinus Calvin Gai (Journal of English Teaching and Learning Issues, 2025)
Language teachers have been interested in reflecting on their teaching and learning practices to improve their professional skills. This study aims to locate, analyze, and synthesize the current state of research on reflective practice (RP) specifically related to English language teaching and learning. Using a set of rigorous criteria that encompassed the quality, content, and types of articles, the researcher selected and reviewed thirty-seven scholarly articles published in fifteen international journals between 2012 and 2022. Employing the holistic approach, the researcher examined the body of RP-related literature, including research goals, methods, contexts, participants, and RP practices. The analysis identified five main themes: collaborative reflection, teaching and learning experiences, reflection techniques, self-study, and written reflection analysis. Each theme was further sub-categorized into different research strands and discussed in light of the relevant literature. As a result, this study has detailed how various forms of RPs were implemented, along with their potential implementation challenges and weaknesses, which should be of interest to language teachers or practitioners who plan to operationalize RP in their pedagogical practices. Methodological implications, empirical voids in RP-related studies, and directions for further research are presented.